Some implications of pricing bundles. (6th March 2013) - Huang, Xiao; Nagarajan, Mahesh; Sošić, Greys
Abstract In this article, we consider a problem in which two suppliers can sell their respective products both individually and together as a bundle, and study the impact of bundle pricing. Four pricing models (centralized, decentralized, coop–comp, and comp–coop) are analyzed with regard to the competition formats and sequences. As one would expect, the firms are always better off when pricing decisions are centralized. However, rather surprisingly, we find that firms may be worse off if the bundle prices are set in a cooperative way; we provide analytical characterization of those instances. Numerical studies show that these insights also hold for some nonlinear demand. © 2013 Wiley Periodicals, Inc. Naval Research Logistics, 2013